Storytelling in English-language anti-trafficking campaign: a cognitive perspective - Палійчук, Е. О. (Studia Philologica, 2019)
The paper focuses on verbal and cognitive aspects of “storytelling” used as a special technique in electronic media messages in the course of social campaigns against human trafficking aimed at raising awareness and competence across vulnerable categories of target audiences. Specifically, there was analysed the cognitive background of the narrative elements employed in the English-language media texts, with major actants of the “human trafficking” conceptual situation distinguished. Based on the outcomes of preliminary groundwork, particularly, on mapping of the conceptual fields of the actants, there were established such properties of the “human trafficking” cognitive construal as iconicity, metaphoricity, visuality, and sensoriality. The shaped narrative model activates its iconicity as a cognitive property in manifestation of the “cobweb-like” construal, with zooming on the image of “victim” as a main character, which is inside the “human trafficking” conceptual model marked with centripetal relations towards “victim” and interrelated links between the conceptual fields of other actants as participants of the situation. Metaphoricity as a property of the said narrative model manifests in mapping of the biological and social domains based on similarity of their components. Therefore, “trafficker” correlates with the image of “spider” within the situation of human trafficking, whereas “victim” gets entrapped into its net”. The metaphors used in narrative components of a media message shape visual images which correlated with the “cobweb-lie” construal based on combinations of image-schemas. Sensoriality as a cognitive property of the narrative model manifests through the vial narrative, where plot components reproduce the “cobweb-like construal” embedded therein. The visual representation of the “human trafficking” model is also enhanced due to tactile and aural images accompanying narration and realized at verbal level in media messages. The outcome of the paper is establishment of a comprehensive narrative model specific to the objectives of raising awareness among vulnerable categories of target audience, with due account of the plot features within its scenario and cognitive properties that predetermine efficiency of the social campaign on the social concern in question.